ANALISIS ETIKA KOMUNIKASI SISWA MELALUI PENDIDIKAN KARAKTER ISLAM DI SMA KOTA TANGERANG SELATAN - Junaidi Junaidi (Edukasi Lingua Sastra, 2018)
This study aims at analyzing the factors affecting students to speak dirty words as an improper action in communication and understanding Islamic Character Building approach to solve their communication ethics. In addition, the study also describes the influence of environment, school and society in their roles on their communication ethics. The populations in this study are all high school students, approximately 10.092 students, in Southern Tangerang using purposive sampling which determines the subjects in the study according to the requirement of data representation to obtain depth of knowledge. The number of samples in this study is 2.5% of the whole population, approximately 252 subjects which are equally distributed on the 12 schools being observed. In this regard, each school represents 21 subjects. Meanwhile, the study applies observation, interviews and documentation to collect the research data. In addition, it uses Domain Analysis, Taxonomy Analysis, Componential Analysis and Analysis of Cultural Themes to process the data. As the result, the frequency of speaking bad words in the study shows 98 % of respondents (247 respondents) stated “frequently”, 1.6 % (4 respondents) said “sometimes” and only 0.4 % (1 respondent) answered “never”. Regarding the dirty words spoken, the study obtains list of words consisting of names of animals such as monkey, dogs or pig, names of sexual organs and terms such as dick or fuck and so on. In addition, it indicates that the partners in the communication are peers, siblings or things that stimulate angers. Meanwhile, the reactions displayed by the partners in the communication vary, such as acting normal, showing anger, laughing or ignoring. At last, the study results in the factors affecting the students to speak dirty words are spontaneity, joke, anger, habits, irritability, response to a mock and environment influence.